2019
DOI: 10.1016/j.jds.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between salivary mutans streptococci, lactobacilli and the severity of early childhood caries

Abstract: Background/PurposeMutans streptococci (MS) and lactobacilli (LB) are associated with dental caries, but the acquisition of these organisms in young children with early childhood caries (ECC) and severe early childhood caries (S-ECC) has only been partly described. The purpose of this study was to evaluate the salivary MS and LB levels of preschool children with ECC and S-ECC, and the correlation of MS, LB levels with caries severity.Materials and methodsThe study population was comprised of children from 3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…e present study utilized stimulated whole saliva as the sample collected from 3-year old children, who showed a high level of cooperation. e results of the study demonstrated that levels of infection with SM and LB in saliva can be used to predict caries risk in children [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…e present study utilized stimulated whole saliva as the sample collected from 3-year old children, who showed a high level of cooperation. e results of the study demonstrated that levels of infection with SM and LB in saliva can be used to predict caries risk in children [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Gram-positive bacteria including streptococci of the mitis [44] and mutans species [45] (which are considered as initial colonizers of the biofilm) then form EPS, which enhance the adherence of other organisms. Emerging evidence shows that acid-producing bacterial species of the genera Veillonella [46], Scardovia [47], Lactobacillus [48], and Propionibacterium [49] could be present in the dental biofilm as colonizers and may induce in cariogenic conditions in the mouth.…”
Section: Dental Biofilmsmentioning
confidence: 99%
“…Recent molecular analyses have revealed the presence of a pathogenic flora that includes bacteria different from streptococci (e.g., Scardovia and Actinomyces) and fungi (e.g., Candida albicans) [58,59]. In addition to S. mutans, Lactobacillus [48], Bifidobacterium [60], and Scardovia species [47] are also considered as caries-associated colonizers. Data from previous studies have suggested that the susceptibility of biofilms to antibiotics, preservatives, or anti-adhesion compounds is closely related to microbial diversity [61][62][63].…”
Section: Dental Biofilmsmentioning
confidence: 99%
“…When Jiang et al (2014) investigated the shifting of microbial profiles in the progression of dental caries, they found that Cryptobacterium , Lactobacillus , Megasphaera , Olsenella , Scardovia , Shuttleworthia , Cryptobacterium , and Streptococcus were increased significantly in cavitated dentin lesions [ 37 ]. Clinical research carried by Liu et al, (2019) found that mutans streptococci and lactobacilli levels were high in cariogenic biofilm due to their capability of acidogenesis at low pH [ 44 ].…”
Section: Diagnosis Of Cariogenic Biofilmmentioning
confidence: 99%